A hybrid analytical-numerical approach for the analysis of salient-pole synchronous generators with a symmetrical damper cage - Nuzzo, Stefano; Bolognesi, Paolo; Galea, Michael; Gerada, C. (2017)
The equivalent circuit approach has been widely exploited for the theoretical analysis of electromagnetic devices. However, in the field of classical wound-field synchronous generators, the presence of the damper cage complicates the analysis of such devices and the accurate prediction of the inherent induced currents is still matter of ongoing research. 12Focus is given to the accurate prediction of the no-load voltage waveform, by implementing a hybrid analytical-numerical model for a specific alternator.